Mechanical Properties of Sandstones after Freeze-Thaw Cycles and Models for Their Strength Prediction - Jiaxu Jin; Junzu Ma; Bing Liang; Guosen Zhang; Shihao Yuan (Advances in Civil Engineering)
In cold regions, rock’s load-bearing capacity will be greatly diminished in severe settings. This research investigates the influence of freezing and thawing on the physical and mechanical characteristics of sandstone, as well as the strength under complicated stress conditions. Uniaxial compression of sandstone samples was performed following freeze-thaw cycles, and the changes in elastic modulus and peak stress of dry sandstone and saturated sandstone were investigated under various freeze-thaw cycles. ANOVA was used to analyze whether there were significant differences between the number of freeze-thaw cycles and the peak strength and elastic modulus. A three-parameter strength prediction model based on σC, k0, and m is created based on the critical failure energy function. Experimental data is utilized to assess the model’s correctness, and the model is used to forecast the strength of dry and saturated sandstone during freeze-thaw cycles. The result indicates that peak stress and elastic modulus of dry and saturated sandstone show a steady attenuation pattern as the number of freeze-thaw cycles increases. Brittle failure is the failure mode of dry sandstone, whereas brittle failure to plastic failure is the failure mode of saturated sandstone. After 60 freeze-thaw cycles, peak stress in dry and saturated sandstone was reduced by 55.3% and 56.8%, respectively. The three-parameter model can predict the triaxial compressive strength of specimens under different confining pressures through the uniaxial compressive strength of specimens with an error range of 1% to 13%.